Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0155583
|View full text |Cite
|
Sign up to set email alerts
|

17-DMAG, an HSP90 Inhibitor, Ameliorates Multiple Organ Dysfunction Syndrome via Induction of HSP70 in Endotoxemic Rats

Abstract: Sepsis is a systemic inflammatory disorder, accompanied with elevated oxidative stress, leading to multiple organ dysfunction syndrome (MODS), and disseminated intravascular coagulation. 17-Dimethylaminoethylamino- 17-demethoxygeldanamycin (17-DMAG), a heat shock protein (HSP) 90 inhibitor, has been reported to possess anti-inflammatory effects. In this study, the beneficial effects of 17-DMAG on lipopolysaccharide (LPS) induced MODS and DIC was evaluated in anesthetized rats. 17-DMAG (5 mg/kg, i.p.) was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Furthermore, HSP70 induction is impaired in ex-vivo lymphocytes of septic patients 31 , and HSP70 is a key determinant of mortality in aged septic hosts 26 . Increased HSP90 is also associated with an acute inflammatory-metabolic stress response in children with sepsis and multiple organ failure 32 , while inhibiting HSP90 ameliorates multiple organ dysfunction syndrome in rats subjected to endotoxemia 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HSP70 induction is impaired in ex-vivo lymphocytes of septic patients 31 , and HSP70 is a key determinant of mortality in aged septic hosts 26 . Increased HSP90 is also associated with an acute inflammatory-metabolic stress response in children with sepsis and multiple organ failure 32 , while inhibiting HSP90 ameliorates multiple organ dysfunction syndrome in rats subjected to endotoxemia 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, anti-inflammatory effects of HSP90 inhibition have been attributed to an induction of HSP70. 28 However, here the effects of EC144 on the inflammasome cannot be attributed to increased levels of HSP70, as its levels did not change with EC144 treatment ( Figure 1G).…”
Section: Resultsmentioning
confidence: 75%
“…Research on different phases of sepsis found that HSPA1B can be considered a serum marker for the acute proinflammatory phase (Gasparotto et al, 2018). Study on Multiple organ dysfunction syndrome in sepsis found that increased HSPA1B has an anti-inflammatory effect (Wang et al, 2016). In rats, raloxifene prevents severe sepsis through induction of HSPA1B with an anti-inflammatory effect (Shen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%